(3Yed ef WH def MHs - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3jfbSe gPG GdcJGH Edi LRFjf ,CMOgeG JYOjO GdeQGV ef QCS Edi bOe , eGYOG eGjJYdb HGdRjfI hKGfjgeG aj GdeQGV GdJi JYe GdHOf s
(3BNQgG (B:s
(3hGeG eG hbY ef GdcdGe ai GdaQhL abO GYJPQ HCf Jdc GdMjd ef OhGYj EZJHGW GdCRhGL hHhGYK ehOGJgf hCSHGH fehGdfSd hGddg YRhLd jLYdfG eef YQa bOQg gh MSHfG hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI KGfjI cGdSGHbIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B162 s
Keywords: (3GdWHs